Faktor-Faktor yang Memengaruhi Keberhasilan Usaha UMKM Pengolahan Buah dan Pengolahan Susu - Bella Nandita; Ma'mun Sarma; Mukhamad Najib (IPB University, 2018)
Micro, small and medium enterprises are able to safe the economy, especially in Indonesia. On the other hand, Indonesia has to face the Asian Economic Community in 2025, that is why micro small and medium enterprises need to understand the factors of business success to compete in to participate in Asian Economic Community. The aims of this research are to know the business characteristics and businessmen characteristics of micro small and medium enterprises fruit and milk processing and to analyze factors affecting business success. Questionnaire surveys have been conducted to 31 respondents for each clusters, milk processing and fruit processing. Data were analyzed by descriptive and multiple linear regression analysis. Multiple linear regression has been conducted in order to examine the relative impact of the identified factors on business success. The factor that affecting business success in fruit and milk processing was entrepreneurial marketing and government policies. The results of this research can be beneficial to relevant agencies.